Quantitative trait genetic linkage analysis of body mass index in familial coronary artery disease. - Specchia, C; Barlera, S; Chiodini, B; Nicolis, E; Farrall, M; Peden, J; Collins, R; Watkins, H; Tognoni, G; Franzosi, MG (2008)
OBJECTIVE: Body mass index (BMI) is one of the most reproducible and commonly used proxies for obesity and is known to be influenced by many environmental causes as well as genetic factors. Identification of susceptibility genes for BMI regulation has been difficult. Reasons for these inconclusive results are both methodological and related to obesity aetiology. A genome-wide linkage analysis was performed to localise Quantitative trait loci influencing BMI in a large cohort collected in the PROCARDIS coronary heart disease study consisting of 1,812 informative families. METHODS: Multipoint linkage analysis for BMI was conducted using both a variance component approach and a model-free regression method, and the resulting LOD scores were compared. RESULTS: The strongest evidence for linkage was detected on chromosomes 13 (LOD 1.6). Other regions showing a LOD score greater than 1 were observed on chromosomes 3, 5, 11, 12 and 15. These results were mainly confirmed by the three different approaches used in the analysis. CONCLUSION: Our study did not find any locus with strongly supporting evidence for linkage to BMI even in such a large sample. Our results confirm the substantial genetic heterogeneity influencing BMI regulation that has emerged from the majority of genome scans so far published.